Great Britain adults' opinions on cycling: Implications for policy. (July 2016) - Tapp, Alan; Davis, Adrian; Nancarrow, Clive; Jones, Simon
Highlights: This paper focuses on policies to encourage cycling in car dominated countries. In spite of the health and environmental benefits cycling remains under-funded in Great Britain. Two large scale surveys of the adult population of Great Britain were undertaken in 2010 and 2013. Attitudes to cycling were found to be broadly positive amongst non cyclists as well as cyclists. Various strategies for influencing policy are debated and discussed. Abstract: In its neglect of cycling, the transport policy history of Great Britain is typical of many car-dependent societies. Policy inertia with respect to sustainable travel may be driven by the assumptions that, firstly, most households have access to the use of a car and are keen to preserve the mobility advantages the current system offers them, and secondly that environmental and health considerations should be subjugated to economic priorities. Thus, in spite of warm words about cycling, pro-car policies tend to dominate. Set against this policy backdrop, and taking the stance that public opinion can influence policy change, this paper reports the results of two large scale surveys of opinions regarding the practice of cycling and its role within society, carried out amongst samples of adults representative of Great Britain, in 2010 and 2013. Results indicated broadly positive opinions relating to cycling as part of society, albeit with these measures dropping slightly between 2010 and 2013. Opinions of cycling were found to be significantly linked to voting intention with, broadly speaking, a gradient of decreasing positivity when moving from the political left to right. These results imply a possible link of 'surface' opinions of cycling being influenced by underlying 'deep-seated' beliefs and values. These results are discussed in terms of policy options for pro-cycling groups wishing to influence the debate. Options include decoupling cycling from underlying belief systems and presenting simply as a form of everyday transport; promoting cycling as a solution to multi-social issues across health, the environment and economic considerations such as lower congestion; the pros and cons of de-marketing car usage; and finally, changing underlying belief systems. It is concluded that pro-cycling advocates may be pleased with the broad support of cycling's contribution to society, but they may need to seek alliances with other environmental or health groups in order to turn these good intentions into genuine policy change.